Seashore Settlement Patterns in the Koné and Naïa Periods: Case Studies from Southwestern New Caledonia. (2nd January 2019) - Sand, Christophe; Grant-Mackie, Jack A.; Campbell, Hamish J.; Turnbull, Jocelyn
Abstract: As part of a geological survey in southwest mainland New Caledonia, potsherds were recorded in the profiles at four coastal sites. Subsequent archaeological investigations at two of these sites have allowed us to diversify the ceramic data and show them to be local variants of Podtanean, Puen, and Plum ceramic types. These are characteristic of production in the southern part of the archipelago during the first millennium BC and first millennium AD. The presence of fishing sites showing no indication of permanent settlements on these seashores, and the clear absence of second millennium AD occupations related to the "Traditional Kanak Cultural Complex", characterized by large sedentary hamlets, illustrate a significant shift in settlement patterns between the first and second millennium AD.